Deblurring Photos With Lucy-Richardson And Wiener Filter Algorithm In Rgba Color - Rustam, Michiavelly; Fahmi, Hasanul; Herry Utomo, Wiranto (Green Publisher Indonesia, 2024)
Photographers and social media influencers create engaging posts every day to captivate their audience with engaging content.Central to success is the need for high-quality images that allow the viewer to clearly perceive and engage with the information being conveyed. However, a persistent challenge in the field of photography is that hand tremors during image capture can result in accidentally blurred photos. In response, I propose a comprehensive solution that leverages the advanced Lucy-Richardson (L-R) and Wiener filter algorithms.This innovative approach is tailored to reduce the effects of blur caused by unstable handling, allowing for sharper, noise-free images. By incorporating these cutting-edge algorithms into their workflows, creators can not only reduce the frustration of blurry footage, but also increase the overall visual impact of their posts, foster deeper connections with their viewers, and create dynamic setting a new standard of excellence in a global world.